2017
DOI: 10.1108/jmd-10-2016-0204
|View full text |Cite
|
Sign up to set email alerts
|

Does team orientation matter? Linking work engagement and relational psychological contract with performance

Abstract: Purpose The cultural transformation introduces team orientation as a powerful tool to reconfigure the human capital to become more productive. The purpose of this paper is to try to uncover two folds: first is to check the direct effects of employees’ work engagement and rational psychological contract on contextual performance and job satisfaction and second is to investigate the moderating effect of team orientation in-between above-stated relationships. Design/methodology/approach The self-administrated q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 43 publications
1
36
0
1
Order By: Relevance
“…Research using the particular scale UWES-9 [Schaufeli et al, 2002] 9 items rated on 7-point scale: 3 vigor items, 3 dedication items, and 3 absorption items 47 studies: Akhtar et al, 2016;Alessandri et al, 2018;Ali et al, 2018;Bakker and Bal, 2010;Bakker et al, 2012;Bal and De Lange, 2015;Castanheira, 2016;Cesário and Chambel, 2017;Chughtai and Buckley, 2011;Dijkhuizen et al, 2016;Eldor and Harpaz, 2016;Eldor, 2017;Findikli, 2015;Fletcher, 2016;Freeney and Fellenz, 2013;Gordon and Demerouti, 2015;Gorgievski and Moriano, 2014;Gutermann et al, 2017;Kapil and Rastogi, 2017;Karatepe, 2011;Karatepe and Olugbade, 2016;Kašpárková et al, 2018;Kataria et al, 2013;Kovjanic and Schuh, 2013;Lathabhavan et al, 2017;Lorente and Salanova, 2014;Maden, 2015;Mäkikangas et al, 2016;Myrden and Kelloway, 2015;Nazir and Islam, 2017;Park et al, 2017;Rahman et al, 2017;Reijseger et al, 2017;Schmitt et al, 2016;Shantz and Alfes, 2013;Shantz et al, 2016;Shuck and Zigarmi, 2015 1 ;Steffens and Haslam, 2014;…”
Section: Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Research using the particular scale UWES-9 [Schaufeli et al, 2002] 9 items rated on 7-point scale: 3 vigor items, 3 dedication items, and 3 absorption items 47 studies: Akhtar et al, 2016;Alessandri et al, 2018;Ali et al, 2018;Bakker and Bal, 2010;Bakker et al, 2012;Bal and De Lange, 2015;Castanheira, 2016;Cesário and Chambel, 2017;Chughtai and Buckley, 2011;Dijkhuizen et al, 2016;Eldor and Harpaz, 2016;Eldor, 2017;Findikli, 2015;Fletcher, 2016;Freeney and Fellenz, 2013;Gordon and Demerouti, 2015;Gorgievski and Moriano, 2014;Gutermann et al, 2017;Kapil and Rastogi, 2017;Karatepe, 2011;Karatepe and Olugbade, 2016;Kašpárková et al, 2018;Kataria et al, 2013;Kovjanic and Schuh, 2013;Lathabhavan et al, 2017;Lorente and Salanova, 2014;Maden, 2015;Mäkikangas et al, 2016;Myrden and Kelloway, 2015;Nazir and Islam, 2017;Park et al, 2017;Rahman et al, 2017;Reijseger et al, 2017;Schmitt et al, 2016;Shantz and Alfes, 2013;Shantz et al, 2016;Shuck and Zigarmi, 2015 1 ;Steffens and Haslam, 2014;…”
Section: Scalementioning
confidence: 99%
“…Research studies using the particular data source Self-reported questionnaire 47 studies: Akhtar et al, 2016;Albdour and Altarawneh, 2014;Alfes and Truss, 2013;Ali et al, 2018;Anitha, 2014;Bal and De Lange, 2015;Barnes and Collier, 2013;Benn et al, 2015;Chong and Lee, 2017;Chughtai and Buckley, 2011;Dalal and Baysinger, 2012;Dash and Muthyala, 2016;Farndale et al, 2014;Findikli, 2015;Fletcher, 2016;Freeney and Fellenz, 2013;Gordon and Demerouti, 2015;Gorgievski and Moriano, 2014;Kapil and Rastogi, 2017;Karatepe and Olugbade, 2016;Kašpárková et al, 2018;Kataria et al, 2013;Kim and Koo, 2017;Lathabhavan et al, 2017;Lorente and Salanova, 2014;Maden, 2015;Mäkikangas et al, 2016;Medlin and Green, 2009;Medlin et al, 2016;Nazir and Islam, 2017;Park et al, 2017;Rahman et al, 2017;Reijseger et al, 2017;Saks, 2006;Shantz and Alfes, 2013;Shantz et al, 2016;Shuck and Zigarmi, 2015;Steffens and Haslam, 2014;Suan Choo, 2016;…”
Section: Data Sourcementioning
confidence: 99%
“…Organizational outcomes such as performance could also be hampered by poor psychological contract. In this vein, consider that Rahman, Rehman, Imran and Aslam's [7] study revealed that work engagement and relational psychological contract have positive relationships with employees' contextual performance and job satisfaction.…”
Section: Many Authorsmentioning
confidence: 99%
“…Essentially, power distribution and consequent power distance is a leadership factor [13] which may orchestrate abuse of the subordinate by the superior Richard, Boncoeur, Chen & Ford, [14] leading to inter-personal aggression and conflict with negative effects to organizational productivity [7]. For example, Iqbal and Rasheed [17] using structural equation-modeling (SEM) technique found that mistreated employees involved in negative reactions and these reactions does not only contained deviating behavior, it also influences them emotionally.…”
Section: Power Distance and Employee Deviancementioning
confidence: 99%
See 1 more Smart Citation